2011
DOI: 10.1142/s1088424611004233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of the most distorted 16π porphyrin: 16π octaisopropyltetraphenylporphyrin (OiPTPP)

Abstract: Previously unreported octaisopropyltetraphenylporphyrin (OiPTPP) was prepared from 3,4-diisopropylpyrrole, an unstable previously unisolated heterocyclic compound. Purification of the free-base 18π porphyrin required conversion to its 18π zinc(II) complex, chromatographic separation, and acid mediated demetalation. Oxidation of the 18π porphyrin with SbCl 5 furnished metal-free 16π octaisopropyltetraphenylporphyrin (OiPTPP). X-ray structural determination revealed that the novel species is the most distorted 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In the opposite sense, an important question is how small of a ring can realize Möbius aromatic molecules. In this context, the tetrapyrrolic porphyrin skeleton has been demonstrated to be not large enough to implement a Möbius twisted topology within a molecule, because the reported [16]­porphyrins and [20]­porphyrins were largely distorted but not twisted and thus were nonaromatic or antiaromatic. N -Fused [22]­pentaphyrins 5a,b′ were larger than porphyrins and might be a potential platform to realize a Möbius twisted topology Scheme ).…”
Section: Möbius Aromatic and Antiaromatic Expanded Porphyrinsmentioning
confidence: 99%
“…In the opposite sense, an important question is how small of a ring can realize Möbius aromatic molecules. In this context, the tetrapyrrolic porphyrin skeleton has been demonstrated to be not large enough to implement a Möbius twisted topology within a molecule, because the reported [16]­porphyrins and [20]­porphyrins were largely distorted but not twisted and thus were nonaromatic or antiaromatic. N -Fused [22]­pentaphyrins 5a,b′ were larger than porphyrins and might be a potential platform to realize a Möbius twisted topology Scheme ).…”
Section: Möbius Aromatic and Antiaromatic Expanded Porphyrinsmentioning
confidence: 99%
“…Immobilization of hydrophilic or zwitterionic polymers on different surfaces is a common strategy to create antifouling surfaces to prevent biofouling. It is generally accepted that polymer coatings offer a strong surface hydration barrier and steric repulsion to prevent the unwanted adsorption of foulants. Hydrophilic polymer coatings (PEG, , polysaccharides, , polyacrylate, , and polyamide , ) achieve surface hydration via hydrogen bonding of polymers with water molecules, whereas zwitterionic polymer coatings (poly­(carboxybetaine methacrylate), poly­(sulfobetaine methacrylate), and poly­(3-(1-(4-vinylbenzyl)-1 H -imidazol-3-ium-3-yl)­propane-1-sulfonate)) achieve electrostatically induced surface hydration where water molecules bind to zwitterionic groups even stronger. The formation of a strong hydration layer at the polymer/water interface offers an energetic barrier to effectively inhibit unwanted foulant adsorption on polymer coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the 1 H NMR and UV–vis spectra as well as calculations of nucleus-independent chemical shifts (NICS) suggested that the OEP-Zn(II) dication is antiaromatic, which is also expected when assuming that Hückel’s rule for aromaticity holds. The detected large blue shift of the UV–vis spectrum and the missing Q-band generally indicate that the porphyrinoid is antiaromatic. For meso-unsubstituted porphyrinoids, the degree of aromaticity can also be estimated from the position of the 1 H NMR signal of the meso -hydrogens . Judging from those experimental data, Hiramatsu et al claimed that the OEP-Zn(II) dication is the strongest antiaromatic porphyrin that has been reported so far.…”
Section: Introductionmentioning
confidence: 99%